Research on the Performance of Arbitrary-Precision Arithmetic Algorithms - Dzisevič, Robert; Šešok, Dmitrij (Jaunųjų mokslininkų darbai, 2017)
Arbitrary-precision arithmetic libraries are analysed and computing experiments were examined in this article. During the experiments, the efficiency of different arbitrary-precision arithmetic libraries (GMP, NTL, FLINT, CLN, Java BigInteger) solving computing tasks which involve the operations of modular multiplication, division and exponentiation were examined.
Keywords: Arbitrary-Precision Arithmetic; Arbitrary-Precision Arithmetic Library; C/C; Java; Factorial; Proth Primes